Evaluating the biocompatibility of ceramic materials for constructing artificial reefs - O’Reilly, Logan M.; Willerth, Stephanie M. (Frontiers in Marine Science, 2024)
Introduction Coastal ecosystems, including reefs, are becoming increasingly threatened as anthropogenic development continues to encroach on intertidal habitats with little initiative to establish ecologically considerate infrastructure. Submerging human-made, shelter-providing structures known as artificial reefs (AR) can contribute to the preservation of these ecosystems. ARs are historically used for promoting the abundance and biodiversity of marine species for aquaculture, conservation, and ecotourism; and are typically made of concretes or metal structures. An AR’s success correlates to its ability to establish a surface layer of microorganisms, such as microalgae and bacteria, known as a biofilm. The productivity of the biofilm can be influenced by material surface properties. It is hypothesized that material pH and porosity affect the rate of biofilm formation. Methods Here - a range of concrete mixtures were cast and submerged in circulating seawater and mass per surface area of biofilm accumulation was measured to evaluate this theory. These mixtures included standard Portland Cement (PC), PC with admixtures of diatomaceous earth (PDC) and limestone (PLC), fine-aggregate high-performance concrete (DUC), and terra cotta (TER). ARs were manufactured as 38mm tall cylinders, 76mm in diameter, and submerged in circulating seawater to evaluate mass per surface area of biofilm accumulation. Results Our results indicate that biofilm formation is directly affected by surface porosity and less-so by pH, as determined by measuring material properties after submersion. We found that the PDC samples were most successful in forming a biofilm despite being more fragile than other concrete samples. Discussion This preliminary study provides insight into how different material properties influence the accumulation of biofilm as a starting point for designing ARs. Future work will investigate the long-term performance of such samples in relevant conditions.